ASSESSMENT OF THE ECOLOGICAL RECLAMATION STATUS OF SOILS USING VEGETATION INDICES - Bakhrom Kholboev (Web of Journals Publishing, 2026)
This article aims to highlight the practical importance of assessing the land reclamation status through geographic information systems, as well as monitoring vegetation cover in regions using vegetation indices.
Keywords: Esri, GIS, NDVI, soil monitoring, vegetation indices.